2016
DOI: 10.1039/c6ta06258j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient polymer solar cells with printed photoactive layer: rational process transfer from spin-coating

Abstract: Scalable solution-manufacturing is at the heart of the promise of low-cost and high throughput manufactured polymer photovoltaics. We propose a rational process transfer from spin-coating which achieves performance parity in blade-coated solar cells with efficiency up to 9.7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 65 publications
3
62
0
Order By: Relevance
“…For example, the comparable PCEs of fullerene-based OSCs prepared by doctor-blading and spin-coating techniques were reported by Zhao et al [16] The OSCs based on poly [4,8-…”
supporting
confidence: 61%
“…For example, the comparable PCEs of fullerene-based OSCs prepared by doctor-blading and spin-coating techniques were reported by Zhao et al [16] The OSCs based on poly [4,8-…”
supporting
confidence: 61%
“…

power conversion efficiency (PCE) of BHJ devices strongly depends on phase separation of the donor and acceptor. [21,22] Moreover, green solvent is a prerequisite for the commercialization of OSCs. To achieve high-performance devices, much effort has been devoted to delicately control the morphology of the active layer (such as the blend ratio between the donor and acceptor, [9][10][11] the type of solvent, [12][13][14] the type and amount of processing additive, [15][16][17] and thermal and solvent annealing [18][19][20] ) to obtain optimal interpenetrated nanoscale phase separation.

…”
mentioning
confidence: 99%
“…[21] Although the abovementioned studies showed promising results, the blade coating method could have limited practicality in manufacturing, especially for roll-to-roll production, due to the method having difficulty in controlling film-thickness and fabricating stripe patterns; and in fact, there has been no report on the roll-to-roll fabrication of blade-coated PSCs. [43][44][45][46][47] Moreover, large fractions of highperformance materials are not suitable for roll-to-roll slot-die coating. The method is classified as a premetered method, so that the thickness of films can be easily and precisely controlled, simply by controlling the solution flow into the head.…”
mentioning
confidence: 99%